PSYCHOMETRIC EVALUATION OF FILIPINO VERSION OF PATIENT SATISFACTION INSTRUMENT - Gil P Soriano; Kathyrine A Calong Calong (Belitung Raya Foundation, Indonesia, 2019)
Background: Patient satisfaction has been revealed to affect patient outcomes and has been used as an indicator for measuring quality in health care. However, there are no culturally appropriate instruments that measure Filipino patient satisfaction receiving nursing care. Objective: The objective of the study is to examine the validity and reliability of the Filipino version of Patient Satisfaction Instrument (F-PSI). Methods: The study utilized a cross-sectional study and included 131 Filipino patients in selected hospitals in Manila and were selected through convenience sampling. The tool undergone cross cultural adaptation following the WHO guidelines. Also, content validity following Davis technique and construct validity through confirmatory factor analysis was done to assessed its validity. To measure its internal consistency reliability, Cronbach’s α, inter-item and total-item correlation was conducted. Results: The construct validity of the Filipino version of PSI showed a good model fit while the item content validity index (I-CVI) ranges from 0.83-1.0 and a scale content validity index (S-CVI) of 0.96. Also, the translated tool showed an acceptable internal consistency reliability. Conclusion: The Filipino PSI is a valid and reliable instrument for measuring satisfaction among Filipino patients. Supplementary studies are needed to ascertain its validity and reliability for clinical use.